Subjective well‐being of NEETs and employability: A study of non‐urban youths in Spain, Italy, and Portugal - Mazzochi, P.; Agahi, O.; Beilmann, M.; Bettencourt, L.; Braziene, R.; Edisherashvili, N.; Keranova, D.; Marta, E.; Milenkova, V.; Higgins, O.; Pizzolante, F.; Prieto-Flores, Ò.; et al. (Politics and Governance, 2024)
Subjective well-being is of paramount importance when support is offered to young individuals seeking employment and social inclusion in general. The present study looks at different dimensions of youth well-being and the growing demands for skills to enable labour market integration. Based on survey data, this article examines the relationships between the role of public employment services in providing support and their impact on the subjective well-being of youth. Specifically, 1,275 not in education, employment, or training (NEET) rural youths from Italy, Portugal, and Spain participated in the survey. Drawing upon Bronfenbrenner’s bioecological model, the current study sets up a model which includes different factors at the micro-, meso-, exo-, and macro-system levels. The results show that non-urban NEETs’ subjective well-being is associated positively with public employment services availability, while the relationship with public employment services interaction and public employment services support is non-significant. A positive and significant relationship emerged also with self-efficacy and social support. Some recommendations for policymakers are discussed.